Effects of Angle Variations in Suspension Push-up Exercise - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Gulmez, I. Effects of angle variations in suspension push-up exercise. J Strength Cond Res 31(4): 1017-1023, 2017This study aimed to determine and compare the amount of loads on the TRX Suspension Trainer (TRX) straps and ground reaction forces at 4 different angles during TRX push-ups. Twenty-eight male (mean age, 24.1 +/- 2.9 years; height, 179.4 +/- 8.0 m; weight, 78.8 +/- 9.8 kg) physical education and sports university students participated in this study. The subjects were tested at TRX angles (0, 15, 30, 45 degrees) during the TRX push-ups. Force data were recorded by a force platform and load cells integrated into the TRX straps. The results show that as the TRX angle was reduced, the load applied to the TRX straps increased and simultaneously the load measured by the force platform decreased. This was true for both the elbow joint changing from flexion to extension and vice versa. When the TRX angle was set at 0 degrees and subjects' elbows were at extension during TRX push-up, 50.4% of the subjects' body weight, and when the elbows were at flexion, 75.3% of the body weight was registered by the sensors on the TRX straps. The results of this study can be used in the calculation of the training load and volume (resistance training programming) during TRX push-up exercises at varying angles.
Keywords: TRX; resistance training; force; MUSCLE-ACTIVATION; TRAINING SYSTEM; SPINE LOAD; INSTABILITY; PATTERNS